NSUN2-mediated m5C methylation of IRF3 mRNA negatively regulates type I interferon responses during various viral infections - Hongyun Wang; Jiangpeng Feng; Cong Zeng; Jiejie Liu; Zhiying Fu; Dehe Wang; Yafen Wang; Lu Zhang; Jiali Li; Ao Jiang; Miao He; Yuanyuan Cao; et al. (Emerging Microbes and Infections)
5-Methylcytosine (m5C) is a widespread post-transcriptional RNA modification and is reported to be involved in manifold cellular responses and biological processes through regulating RNA metabolism. However, its regulatory role in antiviral innate immunity has not yet been elucidated. Here, we report that NSUN2, a typical m5C methyltransferase, negatively regulates type I interferon responses during various viral infections, including SARS-CoV-2. NSUN2 specifically mediates m5C methylation of IRF3 mRNA and accelerates its degradation, resulting in low levels of IRF3 and downstream IFN-β production. Knockout or knockdown of NSUN2 enhanced type I interferon and downstream ISGs during various viral infection in vitro. And in vivo, the antiviral innate response is more dramatically enhanced in Nsun2+/− mice than in Nsun2+/+ mice. The highly m5C methylated cytosines in IRF3 mRNA were identified, and their mutation enhanced cellular IRF3 mRNA levels. Moreover, infection with Sendai virus (SeV), vesicular stomatitis virus (VSV), herpes simplex virus 1 (HSV-1), or Zika virus (ZIKV) resulted in a reduction of endogenous NSUN2 levels. Especially, SARS-CoV-2 infection (WT strain and BA.1 omicron variant) also decreased endogenous levels of NSUN2 in COVID-19 patients and K18-hACE2 KI mice, further increasing type I interferon and downstream ISGs. Together, our findings reveal that NSUN2 serves as a negative regulator of interferon response by accelerating the fast turnover of IRF3 mRNA, while endogenous NSUN2 levels decrease during SARS-CoV-2 and various viral infections to boost antiviral responses for effective elimination of viruses.